Consequences of COVID-19 pandemic over acute bronchiolitis hospitalizations in the center and east of Spain - Juan Manuel Rius-Peris; Jesús Lucas-García; Mónica García-Peris; Pascual Escrivá Tomás; José Miguel Sequí-Canet; Javier González de Dios (Elsevier, 2021)
Introduction: Non-pharmaceutical interventions that have been implemented in southern hemisphere countries because of COVID-19 pandemic declaration in March 2020, have evidenced some unexpected changes in the way of spreading of many other viruses. This study as a part of ECEALHBA's Project, reports the consequences of COVID-19 pandemic over 2020-2021 bronchiolitis epidemic period in the Central and Eastern regions of Spain. Method: Multicenter, observational, descriptive and ambispective study of admitted infants with the diagnosis of bronchiolitis in 16 Spanish hospitals involved in the investigation project. Five epidemic periods previous to COVID-19 pandemic, from 2015 to 2020, were compared with the current one, 2020-2021, in both a qualitative and quantitative manner. Results: Total of 4643 infants were admitted to the participating hospitals along the study period. Pandemic season hospital admissions for bronchiolitis were 94.1% lower than in pre-pandemic period. December and January were peak months for bronchiolitis admissions during pre-pandemic period, but September was the peak month during pandemic year. There was a progressive decrease of admissions from this moment until the end of the follow-up, in April 2021. Rhinovirus has been the commonest etiology for bronchiolitis in 2020-2021 epidemic period of bronchiolitis. Conclusions: Some of the non-pharmaceutical interventions initiated because of COVID-19 pandemic are probably related to the dramatic decrease of bronchiolitis cases in 2020-2021 season. It would be rewarding to purpose novel research to clarify how these simple interventions can be useful, close to vaccines and antiviral drugs, to achieve the goal of avoiding the spread of respiratory viruses in pediatric population. Resumen: Introducción: Las intervenciones no farmacológicas puestas en marcha en territorios del hemisferio sur tras la declaración de la pandemia por COVID-19 en marzo de 2020, han puesto de manifiesto toda una serie de cambios inesperados en la propagación de otros virus. Dentro del proyecto Estudio Colaborativo Español para la Atención de Lactantes Hospitalizados por Bronquiolitis Aguda (ECEALHBA) presentamos este estudio cuyo objetivo ha sido constatar las repercusiones de la pandemia sobre la temporada epidémica de bronquiolitis de 2020 a 2021 en el centro y este de España. Material y métodos: Estudio multicéntrico, observacional, descriptivo y ambispectivo de una muestra de lactantes ingresados por bronquiolitis aguda en alguno de los 16 hospitales españoles participantes en la investigación. Se compararon desde el punto de vista cualitativo y cuantitativo las cinco temporadas epidémicas previas a la pandemia, de 2015 a 2020, con la última de 2020 a 2021. Resultados: Un total de 4.643 lactantes ingresaron en alguno de los hospitales participantes durante el periodo de estudio. Se describe un descenso porcentual de ingresos del 94,1% entre el periodo previo y la temporada epidémica coincidente con la pandemia. Septiembre pasó a ser el mes pico de ingresos en lugar de diciembre y enero como era habitual, con un descenso progresivo de los ingresos a partir de ese momento hasta el final del seguimiento en abril de 2021. El rinovirus, de forma atípica, ha sido el agente responsable de la mayoría de las bronquiolitis en esta última temporada de 2020 a 2021. Conclusiones: Las intervenciones no farmacológicas puestas en marcha como consecuencia de la COVID-19 han hecho desaparecer de su ubicación cronológica habitual la temporada epidémica de bronquiolitis aguda de 2020 a 2021. Cabe plantearse investigaciones específicas para dilucidar el lugar que ocupan estas medidas junto a las vacunas y fármacos antivirales para el control de las infecciones respiratorias de etiología viral en la población pediátrica.